Factors that influence young people's mental health help‐seeking behaviour: a study based on the Health Belief Model. (9th April 2014) - O'Connor, Peter J.; Martin, Brett; Weeks, Clinton S.; Ong, Luzian
Abstract Aim To identify key predictors and moderators of mental health 'help‐seeking behavior' in adolescents. Background Mental illness is highly prevalent in adolescents and young adults; however, individuals in this demographic group are among the least likely to seek help for such illnesses. Very little quantitative research has examined predictors of help‐seeking behaviour in this demographic group. Design A cross‐sectional design was used. Methods A group of 180 volunteers between the ages of 17–25 completed a survey designed to measure hypothesized predictors and moderators of help‐seeking behaviour. Predictors included a range of health beliefs, personality traits and attitudes. Data were collected in August 2010 and were analysed using two standard and three hierarchical multiple regression analyses. Findings The standard multiple regression analyses revealed that extraversion, perceived benefits of seeking help, perceived barriers to seeking help and social support were direct predictors of help‐seeking behaviour. Tests of moderated relationships (using hierarchical multiple regression analyses) indicated that perceived benefits were more important than barriers in predicting help‐seeking behaviour. In addition, perceived susceptibility did not predict help‐seeking behaviour unless individuals were health conscious to begin with or they believed that they would benefit from help. Conclusion A range of personality traits, attitudes and health beliefs can predict help‐seeking behaviour for mental health problems in adolescents. The variable 'Perceived Benefits' is of particular importance as it is: (1) a strong and robust predictor of help‐seeking behaviour; and (2) a factor that can theoretically be modified based on health promotion programmes.